PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 020 PADANG MUTUNG - Nuriman '; Hendri Marhadi; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This Research of background by in reality result of learning IPS Class student of IV SD Country 020 Field of Mutung still not yet shown satisfying value. Intention of this research is to improve result learn IPS Class student of IV SD Country 020 Field of Mutung District of Camphor with applying of model study of type co-operative of Numbered Head Together (NHT). This Research is research of executed class action at Student Class of IV SD Country 020 Field of Mutung District Of Camphor Sub-Province Camphor Province of Riau. Instrument Research consist of Peripheral of used Study at this research of berpedoman at Curriculum Mount Set of Education (KTSP) or which is recognized with Curriculum 2006. Peripheral of study consist of syllabus, RPP, student spread sheet and perception sheet. At first meeting of cycle to I teacher activity reside in at classification " enough"(46%). After meeting both of cycle 1 known by teacher activity reside in at classification "enough"(54%) After done/conducted by repair at cycle to II. Weaknesss which is  to learn at first cycle become repair pokus at meeting to 3 and 4 cycle to II, in the reality happened the make-up of activity which is learn. Pursuant to result of perception of teacher activity reside in at classification " perfect" (66%). After fourth meeting of cycle of II known by teacher activity reside in [at] classification " perfect"(79%). at first meeting of I student activity sikuls at first meeting reside in at classification " enough" (50%). After meeting both of cycle 1 student activity at classification :"high" ( 62%) At third meeting of cycle of II reside in at classification " high" (70%). After fourth meeting of cycle of II known by student activity at classification :" very high" ( 83%). At cycle of I, known that amount of tired student of KKM is 15 student people (75%) from 22 student people. Its meaning happened the make-up of result learn IPS student of elementary score, but there is still 5 student people which not yet reached KKM. At cycle of II, amount of tired student of KKM amount to17 people (85%) from 22 student people Key word: Model Study of type co-operative of Numbered Head Together ( NHT), result learn Social Science.